PENURUNAN KADAR INTERLEUKIN-6 SETELAH PEMBERIAN ALOIN PADA TIKUS JANTAN (RATTUS NORVEGICUS) MODEL ARTRITIS REUMATOID - Wafda Azizah Ilzan; Nadia Purnama Dewi; Rika Amran; Ade Teti Vani; Dessy Abdullah (Yayasan Nusantara Hasana Berdikari, 2025)
Rheumatoid arthritis (RA) is a chronic progressive autoimmune inflammatory disease that damages joint cartilage and synovial tissue. Inflammation in RA activates pro-inflammatory cytokines, including interleukin-6 (IL-6), whose elevated levels contribute to disease progression. Aloe vera contains aloin, an active compound with antioxidant, anti-inflammatory, and anticancer properties.This study aimed to determine the effect of aloin on IL-6 levels in male rats (Rattus norvegicus) with a rheumatoid arthritis model. This experimental study used a pretest-posttest control group design. Twenty-four rats were divided into four groups: K(-) normal control; K(+) positive control induced with CFA and treated with 50 mg Na diclofenac; P I induced with CFA and treated with 500 μg aloin; and P II induced with CFA and treated with 1000 μg aloin. IL-6 levels were measured using a Rat IL-6 ELISA kit and analyzed with an ELISA reader. Statistical analysis showed that aloin significantly reduced IL-6 levels (p<0.05). The 500 μg dose (P I) was the most effective, showing significant differences compared to other groups (p<0.05). Aloin administration reduces IL-6 levels in male rats with rheumatoid arthritis model.